Role of Histone Deacetylases in Drug-Resistant Melanoma: Mechanisms and Therapeutic Implications - Bhuvanesh Sukhlal Kalal (Kinases and Phosphatases, 2025)
Melanoma, known for its aggressive nature and propensity for developing drug resistance, remains a significant clinical challenge. The emergence of resistance to both targeted therapies (like BRAF/MEK inhibitors) and immunotherapies is a major obstacle to achieving durable responses and improving patient survival. HDACs, a class of epigenetic enzymes, modulate gene expression and chromatin structure by removing acetyl groups from histone and non-histone proteins. In melanoma, aberrant HDAC activity contributes to resistance through multiple mechanisms. HDACs influence key oncogenic signaling pathways frequently dysregulated in melanoma, such as the MAPK, PI3K/AKT, and WNT/β-catenin cascades. By altering the activity of these pathways, HDACs promote the survival and proliferation of melanoma cells even in the presence of therapy. Beyond their direct effects on tumor cells, HDACs also play a crucial role in shaping the tumor microenvironment. They can suppress anti-tumor immune responses by reducing immune cell infiltration, modulating cytokine production, and fostering an immunosuppressive milieu. This further contributes to resistance to immunotherapies. Given the central role of HDACs in these resistance mechanisms, HDAC inhibitors (HDACis) have emerged as potential therapeutic agents to restore drug sensitivity. HDACis can induce cell death, inhibit proliferation, and enhance immune responses in melanoma cells. Preclinical and clinical studies have explored the combination of HDACis with existing therapies to overcome resistance. While promising, the clinical application of HDACis is accompanied by challenges, including toxicity, the need for biomarkers to predict response, and the optimization of combination strategies. Ongoing research is dedicated to developing more selective and potent HDACis and to better understand how to effectively incorporate them into melanoma treatment regimens. This review provides a comprehensive overview of the multifaceted ways in which HDACs contribute to melanoma drug resistance and discusses the potential of HDAC-targeted therapies to improve patient outcomes.